Pengaruh Kualitas Produk dan Harga Terhadap Keputusan Pembelian (Studi Pada Konsumen Toko Mbethuk Fashion di Sumenep) - Nursuciati, Andri Wulan; Purnomo, Hadi (Management Department of Economics and Business Of Trunojoyo Madura University, 2023)
This study aims to determine the effect of product quality and price on purchasing decisions at the Mbethuk Fashion Sumenep Store. This research uses quantitative methods. The population in this study are consumers who have purchased and consumers over 17 years of age. Sampling of this study used purposive sampling with a total of 97 respondents, with data analysis techniques using multiple linear analysis.The results of this study are: (1) Product quality influences purchasing decisions at the Mbethuk Fashion Sumenep Store. (2) Prices affect purchasing decisions at the Mbethuk Fashion Sumenep Store. (3) Product quality and price affect purchasing decisions at the Mbethuk Fashion Sumenep Store.